PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP DISIPLIN KERJA KARYAWAN PADA PANDAWA ALL SUITE HOTEL UMALAS, BADUNG - Kade Pande Dimas Prastya; I Made Sunata (Universitas Triatma Mulya, 2022)
Work discipline is the first aspect that affects the performance of an employee. Work discipline is an attitude of respect, respect, obedience, and obedience to the applicable regulations, both written and unwritten. Discipline of an employee is very vital, discipline is needed so that all activities that are being and will be carried out run according to the mechanism determined by the company, so that employees will not take actions that can harm the company. The problem raised in this study is whether leadership style (X1) affects employee work discipline (Y) Pandawa All Suite Hotel, whether motivation (X2) affects employee work discipline (Y) Pandawa All Suite Hotel, and which independent variables are more dominant influence on the work discipline of Pandawa All Suite Hotel employees. The population in this study amounted to 50 people. This study uses the entire population as a sample. The data analysis technique used is data quality test, classical assumption test, multiple linear regression analysis, and t-test analysis. The results of the analysis show that the regression model is Y= -2.623 + 0.064X1 + 0.597X2. The conclusion obtained is that leadership style (X1) has a positive influence on employee work discipline (Y) at Pandawa All Suite Hotel Umalas. Motivation (X2) has a positive influence on employee work discipline (Y) at Pandawa All Suite Hotel Umalas. Motivation (X2) has a more dominant effect on employee work discipline (Y) at Pandawa All Suite Hotel Umalas with a standardized beta coefficient value of (0.958).